Degradation of aniline blue dye in aqueous solution using ozonation as advanced oxidation process: optimization and mechanism - Bhawsar, Aastha; Bhutada, Dinesh; Ghuge, Santosh (Journal of the Indian Chemical Society, 2025)
Aniline blue dye is widely used in various fields, including textile dyeing, biotechnological processes, and analytical chemistry research. However, its release into the environment without proper treatment can have serious adverse effects on human health and the ecosystem, emphasizing the need for effective management and remediation strategies. A limited number of studies are available in the literature employing advanced oxidation processes (AOPs) for the mineralization of aniline blue dye. Therefore, the present work explores ozonation as one of the AOPs to study the degradation aniline blue dye in aqueous solution. The experimental parameters like initial dye concentration, inlet ozone dose and initial dye solution pH were optimized in order to maximize aniline blue dye degradation efficiency. The direct and indirect degradation pathways were analyzed using tbutanol as a radical scavenger. The maximum degradation efficiency of 81.1 % was achieved at optimal experimental conditions of initial dye concentration of 250 mg/L, inlet ozone dose of 18g/h and initial dye solution pH 11 after 30 min of ozonation. The complete colour removal was observed after 15 min of ozonation at the optimized experimental conditions. The presence of radical scavenger t-butanol had no impact on colour removal efficiency indicating direct ozone molecule mechanism. However, COD removal efficiency was decreased with the addition of radical scavenger t-butanol suggesting indirect hydroxyl radical based mechanism. The experimental results suggested that ozonation is an effective and promising method for the degradation of aniline blue dye in aqueous solution, showcasing significant potential for its application in wastewater treatment.
Keywords: Aniline blue dye; Degradation mechanism; Ozonation